The Dogs of CA-SRI-2: Osteometry of Canis familiaris from Santa Rosa Island, California - Hofman, Courtney; Rick, Torben (Ethnobiology Letters, 2014)
Domesticated dogs (Canis familiaris) are an important human companion around the world and have long been a focus of archaeological research. Osteometric analysis of six dogs from a Late Holocene Chumash village on Santa Rosa Island, California indicates that adults, juvenile/young adults, and a puppy were present. Similar to dogs on other Channel Islands, these dogs fall into the large Indian dog category, standing some 43-54 cm tall, with mesaticephalic or mild brachycephalic facial characteristics. No cutmarks were found on the bones, but one of the mandibles was burned. The CA-SRI-2 dogs appear to have eaten high trophic marine foods similar to what humans consumed, documenting the close bond between dogs and humans on the Channel Islands and broader North American Pacific Coast.